FinTech – A Step Ahead or a Force of Creative Destruction in Finance - Pasterny, Zofia (Journal of Finance and Financial Law, 2021)
The purpose of the article/hypothesis. This article aims to introduce the concept of creative destruction in relation to transformative solutions in finance based on the example of FinTech and innovative technologies with special emphasis on blockchain and cloud computing. As a means to reach its objective this paper analyzes in depth the concept of creative destruction originated by Schumpeter in 1940s and translates it to modern business financial environment to present the reader with double-sided effects of introduced changes, their unique and unprecedented character both from the perspective of FinTech and traditional financials intermediares. Methodology. In order to research the effects of innovations on the financial markets the critical study of the foreign literature will be conducted. Results of the research. The conducted considerations displayed a parallel between innovations introduced by FinTech and actions undertaken by traditional financial institutions in order to remain strong players on the financial market. Even though solutions provided by start-ups may debilitate gained trust, which is one of the fundamental cores of finance, and raise questions related to breach of established regulations, they support the market with increased efficiency and variability of products and services. However, it can be easily perceived that advantages of introduced solutions outweigh possible dangers, and financial intermediaries, especially banks, decide to operate on the basis of the enagament model that supposes a synergy with start-up to blend favourable aspects of both of them including banks’ well-established repute and trust along with FinTech’s innovative potential.